Stereotactic body radiation therapy for early-stage non-small-cell lung cancer. Issue 1 (January 2008) - Lo, Simon S; Fakiris, Achilles J; Papiez, Lech; Abdulrahman, Ramzi; McGarry, Ronald C; Henderson, Mark A; Forquer, Jeffrey A; Hoopes, David; Timmerman, Robert D
Stereotactic body radiation therapy has emerged as a novel oncologic therapy and experience with the use of stereotactic body radiation therapy for the treatment of early-stage non-small-cell lung cancer has grown over the last 10 years. This article reviews the radiobiologic, physical/technical and clinical aspects of stereotactic body radiation therapy for early-stage non-small-cell lung cancer. The literature is also reviewed.